Peran Budaya Organisasi terhadap Disiplin Kerja Karyawan Direktorat Produksi PT Krakatau Steel (Persero) Tbk Cilegon - Muhammad Luhung Pribadi; Benny Herlena (Psympathic : Jurnal Ilmiah Psikologi, 2016)
This research aims to study the effect of organizational culture toward  employee work discipline at Directorate Production PT Krakatau Steel (Persero) Tbk Cilegon. The subjects of this research are 115 employees from several divisions at Directorate Production of PT Krakatau Steel (Persero) Tbk Cilegon. The data were collected through cluster sampling technique. Instrument used are  organizational culture scale, and work discipline scale. Data were  analized using correlational test regression analysis technique. The result show that there is significant correlation of organizational culture for employee work discipline at Directorate Production PT Krakatau Steel (Persero) Tbk Cilegon. It is shown by correlation coefficient of regression analysis as R=0,534, with effective contribution R square (R2)= 0,285 or 28,5%, and significance level p = 0,000. Thus, it proves the hypothesis in this research is accepted.